Effect of multi‐walled nanotubes on the interlaminar shear strength of glass fiber/acrylate composite fabricated by stepwise ultra‐violet light curing. Issue 10 (22nd September 2015) - Zhang, Jingjing; Duan, Yugang; Zhang, Xiaohui; Chen, Jie
Abstract : The interlaminar shear strength (ILSS) of glass fiber/acrylate composite with stepwise ultraviolet (UV) light curing was enhanced by adding multi‐walled carbon nanotubes (MWCNTs) into the resin matrix. The maximum content of MWCNTs that can be used in the process was investigated. Differential scanning calorimetry (DSC) results indicated that prepreg with MWCNTs of more than 0.5% by weight was difficult to cure by UV light because of its poor UV light penetration ability. The ILSS was improved obviously due to the improved resin toughness, crack propagation resistance and interfacial adhesion between the resin and glass fibers according to SEM images. Experimental results suggested that the addition of MWCNTs is an effective method to improve the ILSS of UV stepwise curing composites. POLYM. COMPOS., 38:2113–2118, 2017. © 2015 Society of Plastics Engineers